Juramentos y promesas de profesionales de las áreas que trabajan con animales. Fundamentación para una promesa bioética de los científicos que experimentan con animales (Parte I). (2016)
This article reviews some oaths and promises of health professionals of both human animals and non-human animals. It reflects on the interest people have for the professionals taking an ethical oath upon graduation and on the existence of other oaths. It describes and analyzes the Hippocratic Oath, its history and the changes it has had over time. Finally it identifies existing oaths for professionals in the areas who work with animals in countries like Chile, Mexico, Venezuela, Peru and the current oath of zootechnician veterinary doctors and zootechnicians in accordance with article 9 of law 576 of 2000 of Colombia.